PROSES (Waste Alms Program) As an Alternative Innovation for Household Waste Management - Febriawati, Henni; Angraini, Wulan; Suryani, Iis; Kosvianti, Emi; Afriyanto, Afriyanto; Wati, Nopia; Jafrizal, Jafrizal; Yusmaniarti, Yusmaniarti (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Bengkulu Province annual waste accumulation reaches 38,417.16 tons/year, and the volume of waste in Bengkulu City is increasing every day. The total waste entering the Landfills is 648.85 M3, and the condition of the TPA which has been operating for 32 years is expected to decline over the next year. Careless waste disposal will cause water to clog, which further leads to flood. Based on the 2020 Indonesian Disaster Risk Index, Bengkulu province is at the second highest risk for flood after West Sulawesi. This condition will even get worse if the water flow is blocked by waste. Simple action can turn waste into useful objects through waste donation. This study aims to implement waste donation program as an alternative innovation in managing household waste. This was a community-based study with a cross-sectional research design carried out in June and July 2023. The population involved family households in Bengkulu City in 2021. The study samples were selected using a simple random sampling technique which found 542 households. This study has obtained a certificate of ethical approval from the Bengkulu Health Polytechnic Number No. KEPK.BKL/416/06/2023 dated June 30, 2023. Data were analyzed through univariate analysis and analysis of interview results. Most households in Bengkulu City were aged 29-58 years, married, had less than a high school education, unemployed, and had poor levels of  knowledge, attitude, and behavior regarding household waste management. There is a need for commitment from the Environmental Service, District, Village, Head of Neighborhood Units (RT), LPM and Community Figures regarding the implementation of the Waste donation Program. The support of the smallest community unit, namely the Chairman of the Neighborhood Unit, is the key to the success of household waste management among households, especially in sorting organic and inorganic waste. Such practice will help make the waste donation program a success. Waste donation can be an alternative for households in worship and also help reduce the accumulation of waste in Landfills. It is recommended cooperation between the Village Community Empowerment Institution and the Waste Bank in providing routine assistance to the Waste donation Program.